Pengaruh Balance Exercise Terhadap Tingkat Keseimbangan pada Lansia - syarifatul azizah; Yudi Abdul Majid; Septi Ardiyanti (Institut Citra Internasional, 2025)
As the elderly age, many declines affect the ability of the elderly to perform daily activities, increase the risk of falling, and the difficulty of the elderly to maintain their center of gravity when standing upright. Uncontrolled body balance can increase the risk of falls in the elderly due to balance problems. One of the non-pharmacological methods developed to reduce the risk of falls in the elderly is balance training, one of which is Balance Exercise. The purpose of this study was to determine the effect of Balance Exercise on the level of balance in the elderly. This study used a quantitative research method with pre-experimental using one group pre and post design. The sampling technique was purposive sampling with a population of 55 respondents and the number of samples that met the criteria was 15 respondents at the Harapan Kita Social Home in Palembang. Data analysis used the paired T-test. The results of the study obtained a mean value before the Balance Exercise intervention of 38.47 and after the Balance Exercise intervention of 46.07 with a p value of 0.000 <0.05. The conclusion in this study is that there is an effect of Balance Exercise on the level of balance in the elderly before and after the intervention.